PERTANGGUNGJAWABAN PERDATA PERUSAHAAN TERHADAP PENCEMARAN LINGKUNGAN HIDUP BERDASARKAN UNDANG UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP (Studi Penelitian PT. Ciomas Adisatwa) - Muhammad Fachri Hibatullah; Sofyan Jafar; Hasan Basri (JURNAL ILMIAH MAHASISWA FAKULTAS HUKUM UNIVERSITAS MALIKUSSALEH, 2023)
The importance of protecting the environment is one way to carry out the orders of the 1945 Constitution. The Indonesian government has actually shown seriousness in dealing with environmental problems, as evidenced by the making of regulations that discuss the environment, it's just that in the field there are still gaps between das solen and das sein because the rules are very good, in fact not enforced according to expectations. The results of the study show that UUPPLH requires companies that are proven to have polluted to be responsible in the form of civil liability (compensation) and take certain actions, the results of the study also show that PT. Ciomas Adisatwa is also proven to have polluted the river, so that it is subject to administrative sanctions written warnings and forms of responsibility are carried out by increasing supervision, evaluation and taking/checking waste samples regularly in order to anticipate pollution and carry out environmental restoration as a form of corporate moral responsibility because it has make a mistake. Keywords: Civil Liability, Company, Pollution, Environment.